Consumption, cities, and states : comparing Singapore with Asian and western cities - Brooks, Ann, 1952-; Wee, Lionel (Key issues in modern sociology., 2014)
'Consumption, Cities and States' examines the fascinating intersection of consumption, citizenship and the state in a cross-section of global cities in Asia and the West. It focuses on a number of theoretical and empirical analyses: developing and amplifying the intersection of consumption, citizenship and the state in late modernity in relation to a range of cities; examining the concept of the global city as an 'aspirational' category for cities in Asia and the West; and considering case studies which highlight the intersection of consumption and the state. As Ann Brooks and Lionel Wee demon.